Association between the early use of beta-blocker and the risk of sepsis-associated acute kidney injury: A retrospective cohort study using the MIMIC-IV database - Canmin Wang; Yingfang Hu; Yunfeng Song (PLoS ONE, 2025)
Background Sepsis-associated acute kidney injury (SA-AKI) is a common and life-threatening complication in critically ill patients. Studies have shown that the use of beta-blockers improves hemodynamics and the risk of death in patients with sepsis. However, the association between beta-blockers use and the risk of AKI in patients with sepsis remains poorly understood. The present study aimed to evaluate this potential association. Method Sepsis patients for this retrospective cohort study were extracted from the Medical Information Mart for Intensive Care-IV (MIMIC) database. Propensity score matching (PSM) was used to balance the basic characteristics between beta-blocker users and non-users. Univariate and multivariable logistic regression analysis were employed to evaluate the association between early use of beta-blocker and SA-AKI. Odds ratio (OR) and 95% confidence interval (CI) were estimated as effect measurements. Results Totally 4,419 patients with sepsis were enrolled in our study. The follow-up period was from the 24th hour of intensive care unit (ICU) admission to the occurrence of AKI or ICU discharge, with 2,122 (48.02%) cases of developed AKI. After PSM, a lower SA-AKI risk was observed in the early use of the beta-blockers group compared to the non-user group (adjusted OR: 0.80; 95%CI: 0.64–0.99). Similar associations of early use of beta-blockers and SA-AKI were observed in patients younger than 65 years old, male, without comorbidities, and with Simplified Acute Physiology Score II/Charlson comorbidity index scores below the median (all P < 0.05). Conclusion In ICU patients with sepsis, early use of beta-blockers is associated with a reduced risk of AKI, which may help reduce renal impairment and improve survival. Further studies are needed to verify the underlying mechanisms of beta-blockers in the development of SA-AKI.